Do Different Types of Intelligence and Its Implicit Theories Vary Based on Gender and Grade Level? - Ayoub, Alaa Eldin A.; Aljughaiman, Abdullah M.; Alabbasi, Ahmed M. Abdulla; Abo Hamza, Eid G. (Frontiers in Psychology, 2022)
The current study investigated correlations among academic performance, on the one hand, and emotional, social, analytical, creative, and practical intelligence, and their implicit theories of intelligence, on the other hand, in gifted students. Furthermore, it studied the effect of gender and grade on these variables. The participants included 174 gifted fifth (41.4%) and sixth (58.6%) grade students, comprising 53.4% male and 46.6% female students. The following analytical, creative, and practical intelligence tests were administered: the Aurora Battery, the emotional intelligence scale, the implicit theories of intelligence scale, and an assessment scale of students’ performances. The results revealed that there were no significant differences between male and female students in academic performance, different kinds of intelligence, and implicit theories of intelligence. There were, however, significant differences between the fifth and sixth grade students, with the sixth-grade students showing higher levels of all kinds of intelligence, except emotional intelligence. Moreover, the results indicated that the intelligence measures were non-significantly affected by either gender or overall gender–grade interaction. Overall, our results showed that most types of intelligence are related to giftedness, and that there are no gender differences among gifted students on measures of intelligence.